Major problems of adjustment to Philippine culture encountered by Peace Corps volunteers - Kenney, Lester Stewart 1930- (s.n.], 1969)
The study surveyed on the major problems of adjustment to Philippine culture encountered by the Peace Corps Volunteers working in the Visayan Island. The study shows that language is considered the most difficult area of adjustment by the Peace Corps Volunteers, followed by religion and social life.